Immersion in sustainable tourism as an intern (2024)
After an enriching 8-month experience at Beyond the Wall Cartagena, I can affirm that my internship has been a transformative milestone in my training and personal and professional development. This immersion in the world of sustainable tourism has left an indelible mark that will accompany me on my future path. Throughout this journey, I have acquired a wide range of knowledge and skills that allow me to excel in the competitive tourism sector. From empowering local communities and creating authentic experiences, to administrative management within a company, I have also gained a deep understanding of what sustainable tourism entails. Beyond technical knowledge, this experience has given me the opportunity to develop invaluable skills. My capacity for leadership, innovation and problem solving has been strengthened by facing real challenges and making strategic decisions. In addition, I have significantly improved my communication and social skills by interacting with clients, partners and members of the local community in different languages. Having worked in various areas, from administration and business management to customer service and content creation, has provided me with a comprehensive training that prepares me to face the challenges and take advantage of the opportunities in the tourism industry. But beyond professional achievements, this experience has left an indelible mark on my personal growth. The deep knowledge acquired about the culture, traditions and heritage of Cartagena has allowed me to appreciate the richness of this region and the value of preserving it for future generations. In short, my internship at Beyond the Wall Cartagena has been a transformative journey that has shaped my vision and equipped me with the necessary tools to become a professional committed to sustainable tourism. This experience has left an indelible mark on my life and I am eager to continue exploring the opportunities that this exciting field holds for me.